Coordination Clusters of 3d-Metals That Behave as Single-Molecule Magnets (SMMs): Synthetic Routes and Strategies - Maniaki, Diamantoula; Pilichos, Evangelos; Perlepes, Spyros P. (Frontiers in Chemistry, 2018)
The area of 3d-metal coordination clusters that behave as Single-Molecule Magnets (SMMs) is now quite mature within the interdisciplinary field of Molecular Magnetism. This area has created a renaissance in Inorganic Chemistry. From the synthetic Inorganic Chemistry viewpoint, the early years of “try and see” exercises (1993-2000) have been followed by the development of strategies and strict approaches. Our review will first summarize the early synthetic efforts and routes for the preparation of polynuclear 3d-metal SMMs, and it will be then concentrated on the description of the existing strategies. The former involve the combination of appropriate 3d-metal-containing starting materials (simple salts with inorganic anions, metal cardoxylates and pre-formed carboxylate clusters, metal phosphonates) and one or two primary organic ligands; the importance of the end-on azido group as a ferromagnetic coupler in 3d-metal SMM chemistry will be discussed. The utility of comproportionation reactions and the reductive aggregation route for the construction of manganese SMMs will also be described. Most of the existing strategies for the synthesis of SMMs concern manganese. These involve substitution of carboxylate ligands in pre-formed SMMs by other carboxylate or non-carboxylate groups, reduction procedures for the MnIII8MnIV4 SMMs, spin “tweaking”, “switching on” SMM properties upon conversion of low-spin clusters into high-spin ones, ground-state spin switching and enhancing SMM properties via targeted structural distortions, the use of radical bridging ligands and supramolecular approaches. A very useful strategy is also the “switching on” of SMM behavior through replacement of bridging hydroxide groups by end-on azido or isocyanato ligands in clusters. Selected examples will be mentioned and critically discussed. Particular emphasis will be given on the criteria for the choice of ligands.